Unveiling the psychiatric dimensions of hypopituitarism: investigating associations, challenges, and treatment strategies - Butt, Ayesha Imran; Azhar, Muhammad Juniad (Journal of the Pakistan Medical Association, 2024)
Dear Editor, Hypopituitarism is a disorder characterized by insufficient hormone production from the pituitary gland,1,2 manifesting as either pan or partial dysfunction.2 Hypopituitarism is considered a rare disorder by National Institute of Health and there is limited information on its occurrence. A study in Spain demonstrated prevalence of 45.5 cases per 100,000 people.2 Hypopituitarism can be caused by pituitary tumours, head injury, infections, radiation therapy, autoimmune conditions, and genetic abnormalities.2 Hypopituitarism occurs when about 75% of the pituitary gland is affected, causing a spectrum of clinical features from mild to severe.2 Sheehan syndrome, resulting from anterior pituitary ischaemia typically after postpartum haemorrhage, occurs in approximately 5/10,000 births in developing countries.3 Hypopituitarism diagnosis may take a decade or longer due to its diverse clinical presentations.3 As of now, the link between psychotic disorders and hypopituitarism is not completely understood.1 While a few case reports have documented a link between pituitary insufficiency and mental health issues, larger-scale studies are limited in number. Hypopituitarism raises depression and anxiety risk, especially in females and those over 18, with females having tenfold higher risk of depression than males.1 Growth hormone deficiency (GHD) is linked to cognitive impairments, and atypical depression.4 In their 1949 report, Sheehan and Summer noted that one-third of total 143 hypopituitarism patients displayed loss of drive and initiative, and disinterest in social connections.5 Acute psychosis as an initial presentation of hypopituitarism has been reported in cases involving Sheehan's syndrome, traumatic brain injury, and glucocorticoid therapy.5 A 37-year-old pregnant woman diagnosed with Sheehan syndrome exhibited neuropsychiatric symptoms, prompting early diagnosis.3 The 2010 study found that growth hormone therapy improved cognitive function and reduced depression severity in traumatic brain injury patients with GHD. However, discontinuation of therapy led to worsened cognitive function and increased psychiatric symptoms, highlighting the potential benefits of growth hormone therapy and the need for more experimental studies to confirm its effects on neurophysiological and psychiatric wellbeing.4 Adults with Childhood Onset Multiple Pituitary Hormone Deficiency have a notably lower quality of life, underscoring the importance of addressing psychosocial and psychosexual challenges in this population.6 A 60-year-old man with macroprolactinoma and hypopituitarism developed acute psychosis due to non-adherence to cabergoline, treatment with hydrocortisone, and thyroxine lead to full recovery within 48 hours.5 A 41-year-old man with osmophobia improved with sertraline transiently. Later, he was diagnosed with partial hypopituitarism with adrenocorticotropic hormone deficiency. Prednisolone supplementation significantly improved his condition.7 ---Continue